The hagiography of Saint Abercius
1 online resource (viii, 347 pages)
Keywords: "This broad-based critical edition is the first-ever modern translation all of three adaptations of the hagiography of St. Abercius, the 2nd century bishop of Hieropolis, based on one of the most valuable inscriptions of the early church, the Abercius Inscription. This volume features the Greek texts complemented by facing translations for all three versions of the hagiography. The edition also includes introductory chapters, a composite critical text of the inscription, an Epitome, Synaxarion, and Greek/English indices. The reader will have access to the most expansive reconstruction of both the hagiography and the famous inscription based on the oldest traditions-twenty-nine 10th and 11th century manuscripts. The English translations are based on a majority reading, accompanied by an exhaustive Greek text apparatus which preserves the numerous variant readings. The volume provides scholars with new substantive material for research, while the introductory chapters help to familiarise readers interested in early Christianity with the Abercius tradition. The Hagiography of Saint Abercius is an invaluable resource for students and scholars working on early Christianity, early church history, and hagiography, as well as those interested in manuscript transmission"--